An Exploration of the Needling Depth in Acupuncture: The Safe Needling Depth and the Needling Depth of Clinical Efficacy - Jaung-Geng Lin (Evidence-Based Complementary and Alternative Medicine, 2013)
Objective. To explore the existing scientific information regarding safe needling depth of acupuncture points and the needling depth of clinical efficacy. Methods. We searched the PubMed, EMBASE, Cochrane, Allied and Complementary Medicine (AMED), The National Center for Complementary and Alternative Medicine (NCCAM), and China National Knowledge Infrastructure (CNKI) databases to identify relevant monographs and related references from 1991 to 2013. Chinese journals and theses/dissertations were hand searched. Results. 47 studies were recruited and divided into 6 groups by measuring tools, that is, MRI, in vivo evaluation, CT, ultrasound, dissected specimen of cadavers, and another group with clinical efficacy. Each research was analyzed for study design, definition of safe depth, and factors that would affect the measured depths. Depths of clinical efficacy were discussed from the perspective of de-qi and other clinical observations. Conclusions. Great inconsistency in depth of each point measured from different subject groups and tools exists. The definition of safe depth should be established through standardization. There is also lack of researches to compare the clinical efficacy. A well-designed clinical trial selecting proper measuring tools to decide the actual and advisable needling depth for each point, to avoid adverse effects or complications and promote optimal clinical efficacy, is a top priority.